MECHANICAL PROPERTIES, WATER ABSORPTION, AND FAILURE ANALYSES OF KENAF FIBER REINFORCED EPOXY MATRIX COMPOSITES - Yusuff, Ikhwan; Sarifuddin, Norshahida; Mohamad Badari, Siti Norbahiyah; Mohd Ali, Afifah (IIUM Engineering Journal, 2021)
The potential of natural fibers as one of the candidate materials in the production of fiber-reinforced polymer composites have been widely investigated. In the current study, natural fiber-reinforced polymer composite was fabricated by employing woven kenaf fiber as a reinforcing agent with epoxy resin that acts as a matrix constituent. This composite sample was fabricated using the application of the vacuum infusion method in which the content of kenaf fibers was varied from 30 vol.%, 40 vol.%, and 50 vol.%. The effects of different fiber loadings toward mechanical and physical properties as well as failure properties of kenaf composite were then evaluated. Kenaf composites were subjected to mechanical tests including tensile and flexural tests. The result shows that the highest tensile strength and modulus were attained at 76.67 MPa and 2.31 GPa, respectively with kenaf composite fabricated with 40 vol.% fiber content. Meanwhile, the highest flexural strength and modulus were recorded at 61.24 MPa and 4.20 GPa, also corresponding to kenaf composite that is loaded with 40 vol.% fibers. Fiber pull-out failure was able to be detected in fabricated kenaf composites. Meanwhile, fiber breakage resulting from flexural failure could also be observed in the kenaf composite samples. Apart from that, it was found that as more kenaf fiber was loaded in the composites, the rate of water absorption tended to increase where the highest rate of water absorption was found at 43.33%, displayed by kenaf composite with 50 vol.% of fiber content. ABSTRAK: Potensi gentian semula jadi sebagai salah satu bahan dalam penghasilan komposit polimer bertetulang gentian telah banyak dikaji. Dalam kajian terkini, komposit polimer yang diperkuat dengan gentian semula jadi dibuat dengan menggunakan serat kenaf tenunan sebagai agen penguat dan resin epoksi yang bertindak sebagai matriks. Sampel komposit ini dibuat menggunakan kaedah infusi vakum di mana kandungan serat kenaf digunakan adalah 30 vol.%, 40 vol.%, dan 50 vol.%. Kesan kandungan serat yang berbeza terhadap sifat mekanikal dan fizikal serta sifat kegagalan komposit kenaf kemudiannya dinilai. Komposit Kenaf diuji dengan ujian tegangan dan lenturan. Hasilnya menunjukkan bahawa kekuatan tegangan dan modulus tertinggi dicapai pada 76.67 MPa dan 2.31 GPa, milik komposit kenaf yang dibuat dengan kandungan serat 40 vol.%. Sementara itu, kekuatan dan modulus lenturan tertinggi dicatatkan pada 61.24 MPa dan 4.20 GPa juga milik komposit kenaf yang dimuatkan dengan serat 40% vol. Kegagalan serat terkeluar dapat dikesan pada komposit kenaf buatan. Sementara itu, kerosakan serat akibat kegagalan lenturan juga dapat dilihat pada sampel komposit kenaf. Selain itu, didapati bahawa semakin banyak serat kenaf yang dimuatkan dalam komposit, cendurung meningkatkan kadar penyerapan air di mana kadar penyerapan air tertinggi didapati pada 43.33% yang ditunjukkan oleh komposit kenaf dengan kandungan serat 50% vol.